Cinta, Dendam, dan Ambiguitas: Kajian Dekonstruksi Derrida dalam Novel Romantic Revenge Karya Aura_Urak - Nani, Nani; Wajdi, Fathullah; Hajrah, Hajrah; Syawal, Sahrul (Kajian Linguistik dan Sastra, 2025)
This article discusses the fragmentation of meaning in Aura_Urak's novel Romantic Revenge through Jacques Derrida's deconstruction approach. This study is motivated by the complexity of the relationship between love and revenge in literary texts that are laden with ambiguity of meaning. The research aims to reveal the instability of meaning in the love narrative presented, as well as how these meanings are always deferred, fragmented, and open to multiple interpretations. The method used is textual analysis with a post-structuralist approach, referring to Derrida's theory of deconstruction and Roland Barthes' concept of the death of the author. The findings reveal that the novel presents a non-linear dynamic of meaning, where love does not appear as a singular concept but as a fragile, contradictory, and context-dependent emotional experience. Thus, readers play a central role in shaping and negotiating the meaning of the ambiguous and paradoxical narrative. Abstrak Artikel ini membahas fragmentasi makna dalam novel Romantic Revenge karya Aura_Urak melalui pendekatan dekonstruksi Jacques Derrida. Kajian ini dilatarbelakangi oleh kompleksitas relasi cinta dan dendam dalam teks sastra yang sarat ambiguitas makna. Penelitian bertujuan mengungkap ketidakstabilan makna dalam narasi cinta yang ditampilkan, serta bagaimana makna-makna tersebut selalu tertunda, terpecah, dan terbuka terhadap interpretasi jamak. Metode yang digunakan adalah analisis tekstual dengan pendekatan post-strukturalisme, mengacu pada teori dekonstruksi Derrida dan konsep kematian pengarang Roland Barthes. Hasil kajian menunjukkan bahwa novel ini menyuguhkan dinamika makna yang tidak linier, di mana cinta tidak tampil sebagai konsep tunggal melainkan sebagai pengalaman emosional yang rapuh, kontradiktif, dan tergantung pada perspektif pembaca. Dengan demikian, pembaca memainkan peran sentral dalam membentuk dan menegosiasikan makna dari narasi yang ambigu dan penuh paradoks.